Framework Design of Power Grid Planning and Design Platform - Tian Tian; Hanghai Hu; Yunfeng Cao; He Hao (Institute of Advanced Engineering and Science, 2014)
Power grid planning and design platform is an integration power grid planning and design and technical-support platform system,serving in power grid companies at all levels and the planning and design unit multistage users for collaborative planning design, comprehensively supporting planning and design basis data management, major network planning, distribution network planning, project planning, planning achievements management and project review. Based on the experience of power grid planning and power grid information construction, an overall architecture design scheme of power grid planning and design platform is presented in this paper. The paper emphasizes the data platform design, and expounds the characteristics of the design platform, which provides the reference and basis for the power grid planning and design platform construction. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5111